Biodegradation of used lubricating oil by microbes isolated from pristine soil environment - Abioye, O.P.; Abdul Raman, Abdul Aziz; Agamuthu, Pariatamby (Faculty of Science, University of Malaya, 2012)
Pollution of soil by used lubricating oil is a common phenomenon in most cities in developing countries. This may pose a great threat to the environment and human being at large. Potential of hydrocarbon utilizing bacteria and yeast isolated from pristine (uncontaminated) soil to degrade used lubricating oil was studied in broth culture for 28 days at 30 ± 2 °C. Four isolates (Pseudomonas aeruginosa, Micrococcus luteus, Trichosporon mucoides and Candida tropicalis) were used for the study. The highest percentage (40.6%) of total petroleum hydrocarbons (TPH) and hydrocarbon fractions degradation was recorded by C. tropicalis followed by T. mucoides throughout the study period, compared to those recorded by P. aeruginosa and M. luteus. Thus, pointing out the potential of the yeast species (Candida tropicalis) in biodegradation of used lubricating oil from soil environment.